PERAN PERCEIVED ORGANIZATIONAL SUPPORT TERHADAP WORK ENGAGEMENT MELALUI SELF EFFICACY DAN ENTREPRENEURIAL BRICOLAGE SEBAGAI MEDIASI - Salsabilah, Kartika; Prasetyoning Tyas, Ari Anggarani Winadi (POLITEKNIK LP3I JAKARTA, 2026)
Employees are valuable assets whose work engagement must be maintained, especially in a dynamic creative industry such as Malacca Advisory, where work engagement is influenced by various factors including perceived organizational support. This study aims to analyze the role of perceived organizational support on work engagement with self-efficacy and entrepreneurial bricolage as mediators among 60 employees of Malacca Advisory at Malacca Enterprise Indonesia. Using purposive sampling with a census method, data were collected through an online questionnaire and analyzed using Structural Equation Modeling – Partial Least Square. The results showed that perceived organizational support has a positive and significant effect on self-efficacy, entrepreneurial bricolage, and work engagement. Entrepreneurial bricolage has a positive and significant effect on work engagement and is proven to partially mediate the relationship between perceived organizational support and work engagement, while self-efficacy has no significant direct or mediating effect. The implication of this research is that organizations need to strengthen perceived employee support, clarify work structures, and encourage bricolage behavior to enhance work engagement, particularly in the context of creative industries with limited resources.